2021
DOI: 10.1021/acsami.1c07822
|View full text |Cite
|
Sign up to set email alerts
|

Benzobis(Thiazole)-Based Conjugated Polymer with Varying Alkylthio Side-Chain Positions for Efficient Fullerene-Free Organic Solar Cells

Abstract: Alkylthio groups can be used to modulate energy levels and molecular packing of organic semiconductors, which makes it important in the design of materials for organic solar cell. However, its effect has not been sufficiently exploited as most of the studies report introducing an alkylthio group to the donor unit and seldom to the acceptor unit of donor−acceptor conjugated polymers. In this report, two alkylthio-substituted polymers, namely, PBB-TSA and PBB-TSD, with benzo[1,2-d:4,5-d′]bis(thiazole) (BBT) as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…In 2021, Bao et al synthesized two alkylthio‐substituted polymers, PBB‐TSA and PBB‐TSD, whose alkylthio side chains were, respectively, substituted on the BBTz unit and BDT unit to modulate energy levels and molecular packing. [ 102 ] Compared to PBB‐H, PBB‐TSA and PBB‐TSD showed upshifted and downshifted energy levels, respectively. Both polymers exhibited dominant face‐on orientation, while PBB‐TSD exhibited higher crystallinity compared to PBB‐TSA.…”
Section: Photovoltaic Materials Based On Btz and Bbtzmentioning
confidence: 99%
“…In 2021, Bao et al synthesized two alkylthio‐substituted polymers, PBB‐TSA and PBB‐TSD, whose alkylthio side chains were, respectively, substituted on the BBTz unit and BDT unit to modulate energy levels and molecular packing. [ 102 ] Compared to PBB‐H, PBB‐TSA and PBB‐TSD showed upshifted and downshifted energy levels, respectively. Both polymers exhibited dominant face‐on orientation, while PBB‐TSD exhibited higher crystallinity compared to PBB‐TSA.…”
Section: Photovoltaic Materials Based On Btz and Bbtzmentioning
confidence: 99%
“…[37] Polymers based on the former are well-studied, [37] while those with the latter have been poorly developed. [38][39][40][41][42][43][44] Chen et al have demonstrated 4,8-BBTz based polymers could obtain high mobilities, long exciton lifetimes, pure domains, and dominant face-on orientation when blending with Y6, thus delivering decent PCEs over 15%. [40] The results demonstrated the application poten-tial of BBTz-based polymers in SMA-based OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The device performance of organic photovoltaics (OPVs) has improved remarkably owing to the recent development of novel light-harvesting materials. Nonfullerene structured acceptors (NFAs) such as ITIC and Y6, employed as n -type materials in OPVs, provide complementary absorption with p -type conjugated polymers (CPs) and enable one to maximize light-harvesting capabilities and enhance the power conversion efficiency (PCE). The efficacy of NFAs is more pronounced in OPVs with a bulk-heterojunction (BHJ) architecture where NFA ( n -types) and CP ( p -types) are intermixed at a nanoscale. , Therefore, the development and application of new NFAs are of interest to further improve the OPV performance. Because NFAs are adopted as electron acceptors in BHJ OPVs, their working mechanism is the same as that of fullerene derivatives. , This indicates that managing the film morphology composed of CPs and NFAs, such as the interfacial area, domain size, and crystallinity of individual domains, has a decisive effect on the OPV performance. , Therefore, understanding the interface properties between CPs and NFAs is essential for devising efficient light-harvesting materials for BHJ-type OPVs.…”
Section: Introductionmentioning
confidence: 99%